Nutritive value of forages as affected by soil and climatic differences - Richardson, D.; Banbury, Evans E.; Erhart, A.B.; Williams, G.; Russ, Oliver G.; Smith, K.F.; Loper, D.C.; Harbers, L.H.; Cox, R.F. (Kansas Agricultural Experiment Station, 2011)
This is the second test to measure differences, if any, in performance of cattle in various parts of Kansas due to location, soil, climate, rainfall and/or local feed. Forty-eight Hereford steer calves from the same herd averaging 454 pounds each were divided as uniformity as possible into four groups of 12 animals. One group was assigned to each of the four locations: Colby, Garden City, Manhattan and Mound Valley.
Keywords: Beef; Forages; Soil; Climate